THE CHANGE OF THE ROLE OF SCIENCE AND SCIENTIFIC EDUCATION IN THE MODERN SOCIETY OF THE 21st CENTURY - VITALY G. Gorokhov (Высшее образование в России, 2016)
The modern situation in our country is characterized by a predominance of a new bureaucracy in the spheres of science and higher education. This bureaucracy grounds its “reformatory” activity with different social myths. In this article we criticize these myths.